FORMATION OF INTEGRATION TRANSFORMATIONS IN THE PARADIGM OF TRANSITIVE ECONOMY - A. Kozlov (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the integration change in the specificity of transnational economic entity as a strategic opportunity of developing economy under the condition of interrelation and interpenetration in the paradigm of integration economic activity. The transformation of the institutional attractiveness of an economic entity affects the structure of the space of economic interaction, it allows to identify areas of sustainable development for a transnational company. Internationalized capital is determined, in its aspiration, to have a profound impact on the stimulation of activity in the field of integration transformation of a transitive nature in economic relations.